Association between vertical and horizontal force-velocity-power profiles in netball players - Escobar-Álvarez, J. A.; Fuentes-García, J. P.; Viana-da-Conceição, F. A.; Jiménez-Reyes, P. (Journal of Human Sport & Exercise, 2022)
Netball is a collective sport characterized by intermittent high-intensity actions. Therefore, the players must develop high levels of relative bilateral and unilateral strength and power for both improve performance and also reduce injury risk. The purpose of this study was (i) to provide a reference about the mechanical outputs obtained in the vertical (jumping) and horizontal force-velocity-power (FVP) profile and (ii) observe their relationship, besides the performance in jumping and sprinting in amateur female netball players (age = 24.3 ± 3.2 years, BM = 64.5 ± 5 Kg, height = 172.5 ± 6.2 cm). The variables for both FVP profiles (theoretical maximal force (F0), theoretical maximal velocity (V0) and theoretical maximal power output (Pmax)) were measured with two scientifically validated apps for iOS (My Jump 2 and My Sprint). Our results in regards to the vertical FVP suggest that netball players have low force deficit (36.2 ± 14.6%) and individualized training based on F-V profiling could be beneficial to address their deficit. The moderate correlations found for performance, V0 and Pmax suggest that the improvement in one of the skills (jumping or sprinting) may produce some positive adaptation to the other. However, no association was found in the force production (F0) of the lower limbs for both FVP. Therefore, we recommend that netball players must train specifically ballistic actions in the vertical (jumping) and horizontal direction (sprinting) due to the specificity of both skills and the consequent impact of them on netball performance.